The Analgesic Effect And Functional Improvement Produced by Radio-Frequency Ablation of Genicular Nerves in Patients with Advanced Knee Osteoarthritis - Akhlaque, Uzma; Ayaz, Saeed Bin; Ahmad, Khalil; Shoaib, Muhammad; Younas, Umer; Tassadaq, Naureen (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the efficacy of radiofrequency ablation for treating pain in patients with advanced knee osteoarthritis. Study Design: Quasi-experimental study. Place and Duration of Study: Pain Clinic of Armed Forces Institute of Rehabilitation Medicine Rawalpindi, from Sep 2019 to Feb 2020. Methodology: Patients of more than 50 years of age, with grade III and IV Kellgren-Lawrence grades of knee osteoarthritis and at least a score of 4 for three months on the numerical rating scale were included in the study. Measurements were taken on the numerical rating scale and Western Ontario and McMaster universities osteoarthritis index before and four weeks after fluoroscopy-guided radiofrequency ablation of three genicular nerves around the knee joint. . Results: Fifty patients (mean age: 62 ± 6.5 years) were included in the study. The median numerical rating scale scores before and after intervention were 9 (Interquartile range: 7-10) and 5 (Interquartile range: 2-8), respectively (p<0.001). The mean Western Ontario and McMaster universities osteoarthritis index scores before and after intervention were 76.7 ± 13.4 and 50.3 ± 18, respectively (p<0.001). No complications were reported. The reduction in numerical rating scale, Western Ontario and McMaster universities osteoarthritis index scores after the intervention were significantly better in females than in males (p=0.023 and p=0.012 respectively); however, no significant change was observed for the right and left knee or grades of knee osteoarthritis (p>0.05). Conclusion: Radiofrequency ablation of genicular nerves around the knee joint significantly improves pain, stiffness and body function in patients with advanced knee osteoarthritis .........................